Expressed motives of amateur karate and taekwondo athletes for sport participation - Umit Dogan Ustun; Halil Bıskın; Nurullah Emir Ekıncı (Türk Spor ve Egzersiz Dergisi)
This study aimed to investigate amateur karate and taekwondo athletes' participation motivation mutually. A total of 206 amateur karate and taekwondo athletes voluntarily participated in the study. In the study to collect data Turkish version of Participation Motivation Questionnaire (PMQ) used. The questionnaire consisted of 30 items and eight factors. In the evaluation of data in addition to descriptive statistical methods, MANOVA was used to identify significant differences. As a result, according to descriptive statistics, while the most important motive for sport participation was found to be as "skills development," the least important motive was found to be as "friend" for both karate and taekwondo athletes. But MANOVA results did not reveal any significant differences (p gt;.05). This result is thought to be because of both karate and taekwondo are individual sport branches and requires both skill and talent.